Social need for environmental protocols with fish how biomonitors of heavy metals in aquatic ecotoxicology - Argota-Pérez, George (2023)
The purpose of the study was to describe the social need for environmental protocols with fish as biomonitors of heavy metals in aquatic ecotoxicology. It is considered that the regulatory standards for environmental pollution do not allow the analysis of the effects of heavy metals on aquatic biota. In view of this limitation, it is recognized that some organisms such as fish are used as biomonitors, as they contribute to evaluate the anthropogenic damages generated in the aquatic ecosystem. Despite the advantages of biomonitors, the regulatory standards still do not consider comparative patterns of the bioaccumulation potential of heavy metals in fish as a biomonitoring organism. Any biomonitoring with fish, being a scientifically based system, will allow environmental monitoring to preserve the sustainability of aquatic ecosystems.